These ghosts are family [compact disc, unabridged] : a novel - Card, Maisy (Simon & Schuster Audio, 2020)
Stanford Solomon has a shocking, thirty-year-old secret. And it's about to change the lives of everyone around him. Stanford Solomon is actually Abel Paisley, a man who faked his own death and stole the identity of his best friend. And now, nearing the end of his life, Stanford is about to meet his firstborn daughter, Irene Paisley, a home health aide who has unwittingly shown up for her first day of work to tend to the father she thought was dead. Revolving around the consequences of Abel's decision the story of the Paisley family is told from colonial Jamaica to present day Harlem. There is Vera, whose widowhood forced her into the role of single mother. There are two daughters and a granddaughter who have never known they are related. And there are others, like the house boy who loved Vera, whose lives might have taken different courses if not for Abel Paisley's actions.